THE ABUNDANCE OF ZOOPLANKTON IN PEAT SOIL PONDS OF CATFISH (Patin) WAS GIVEMIXED OF HUMAN’S FECES AND COW’S FECES BIOFERTILIZER - ismet, M.Yorasoki; Syafriadiman, Syafriadiman; Hasibuan, Saberina (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
Abtrac The research was carried out in October to November 2019, located on the Peatlands in the Pine Farmers Road, Kualu Nenas Village, Tambang District, Kampar Regency, Riau Province. Observation of zooplankton have been done in the Laboratory of Environment Quality of Aquaqulture, Biology Chemistry Laboratory, Fisheries and Marine Faculty. The purpose of this study was to determine the effect of a mixture of human feces biofertilizer with cow feces that is best for increasing zooplankton abundance, growth and survival of catfish (Pangasius sp) in peat ponds. The research method is an experimental method, using a completely randomized design (CRD) of one factor (a mixture of human feces biofertilizer and cow feces biofertilizer), 5 (five) levels of treatment, were P0: (control); P1 (Giving biofertilizer 20% human feces + 80% cow feces); P2 (Giving biofertilizer 40% human feces + 60% cow feces); P3 (Giving biofertilizer 60% human feces + 40% cow feces); P4 (Giving 80% human feces + 20% cow feces), 3 (three) replications. The results of this study that was P4 (Giving 80% human feces + 20% cow feces) to produce zooplankton abundance (8889 ind / l), absolute weight growth (17.3 g), absolute length growth (4.4 cm) and survival of catfish (86%) compared to (P3, P2, P1 and P0). The water quality during the study was quite good, temperature 26-29oC, pH 6-7, DO 5-6 mg / l, Nitrate 3.77 ppm, Orthoposphate 4.51 ppm. Keywords: Biofertilizer, zooplankton abundance, peat soil, Pangasius sp.